PENGARUH SELF AFFICACY TERHADAP HASIL BELAJAR MATEMATIKA DASAR MAHASISWA PGMI STAI DARUL ULUM KANDANGAN - Nor Asyriah (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
Abstract Mathematics as one part of the disciplines studied at every level of education. The learning process will occur effectively if all internal factors and external factors are regarded by the teacher. One of the internal factors is self-efficacy which includes task difficulties, anxiety, stress, strength and belief overcoming. This study aims to determine whether self-efficacy affects basic mathematics learning achievement for the third semester students PGMI of STAI Darul Ulum Kandangan for the academic year 2020/2021. This research is a correlational research with a quantitative approach. The data collection instrument used was a self-efficacy questionnaire, the final grades of basic mathematics courses obtained through documents and interview guidelines. The analytical technique used is descriptive statistical analysis (simple correlation coefficient). The sample taken was was 40 students of PGMI STAI Darul Ulum Kandangan. The results of the analysis based on the product moment analysis test stated that there was no significant effect of self-efficacy on the basic mathematics learning achievement the third semester students PGMI of STAI Darul Ulum Kandangan for the academic year 2020/202. the result showed that the t value was 0.726 at the 5% significance level and the t. table was 2.021. because student self-efficacy is effected by other factors, namely online learning. Keywords: Self Efficacy, learning achievement, basic mathematic, PGMI